$(1+m^2)x^2 + 2cmx + (c^2 \,–\, a^2) = 0$ is a quadratic equation and the roots of this equation are same.

01

Due to the equal roots of the quadratic equation, the discriminant of the quadratic equation is zero. For example, $ax^2+bx+c = 0$ is a quadratic equation in general form. The discriminant is $b^2-4ac$ and it is zero due to equal roots.

$b^2 \,-\, 4ac = 0$

02

Compare the quadratic equation $(1+m^2)x^2 + 2cmx + (c^2 \,–\, a^2) = 0$ with standard form quadratic equation $ax^2+bx+c = 0$.

$a = 1+m^2$, $b = 2cm$ and $c = (c^2 \,–\, a^2)$. Substitute these values in discriminate of the quadratic equation.

$b^2 \,-\, 4ac = 0$

$\implies {(2cm)}^2 \,-\, 4 \times (1+m^2) \times (c^2 \,–\, a^2) = 0$

$\implies 4c^2m^2 \,-\, 4 \times (c^2 \,–\, a^2 + m^2 c^2 \,–\, m^2 a^2) = 0$

$\implies 4c^2m^2 \,-\, 4c^2 + 4a^2 \,-\, 4m^2c^2 + 4m^2a^2 = 0$

$\implies 4c^2m^2 \,-\, 4c^2 + 4a^2 \,-\, 4c^2m^2 + 4m^2a^2 = 0$

$\require{cancel} \implies \cancel{4c^2m^2} \,-\, 4c^2 + 4a^2 \,-\, \cancel{4c^2m^2} + 4m^2a^2 = 0$

$\implies \,-\, 4c^2 + 4a^2 + 4m^2a^2 = 0$

$\implies 4a^2 + 4m^2a^2 = 4c^2$

$\implies 4c^2 = 4a^2 + 4m^2a^2$

$\implies 4c^2 = 4a^2(1 + m^2)$

$\require{cancel} \implies \cancel{4}c^2 = \cancel{4}a^2(1 + m^2)$

$\implies c^2 = a^2(1 + m^2)$

$\therefore \,\,\,\,\,\, c^2 -a^2(1 + m^2) = 0$

Latest Math Topics

Latest Math Problems

A best free mathematics education website for students, teachers and researchers.

Learn each topic of the mathematics easily with understandable proofs and visual animation graphics.

Learn how to solve the maths problems in different methods with understandable steps.

Copyright © 2012 - 2021 Math Doubts, All Rights Reserved